2011
DOI: 10.1186/cc10277
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related outcome difference is related to course of sepsis on mixed ICUs: a prospective, observational clinical study

Abstract: IntroductionImpact of gender on severe infections is in highly controversial discussion with natural survival advantage of females described in animal studies but contradictory to those described human data. This study aims to describe the impact of gender on outcome in mixed intensive care units (ICUs) with a special focus on sepsis.MethodsWe performed a prospective, observational, clinical trial at Charité University Hospital in Berlin, Germany. Over a period of 180 days, patients were screened, undergoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 32 publications
5
96
1
2
Order By: Relevance
“…to evaluate the reliability of time assessments for delay from meeting the MET criterion to time of ICU admission; the Lin correlation coefficient was 0.94. Modified early warning scores (MEWS) were calculated for the time E vidence [1][2][3] indicates that women have a higher mortality after admission to an intensive care unit (ICU) than do men. The reasons for this difference are poorly understood, and many questions remain unanswered.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…to evaluate the reliability of time assessments for delay from meeting the MET criterion to time of ICU admission; the Lin correlation coefficient was 0.94. Modified early warning scores (MEWS) were calculated for the time E vidence [1][2][3] indicates that women have a higher mortality after admission to an intensive care unit (ICU) than do men. The reasons for this difference are poorly understood, and many questions remain unanswered.…”
Section: Data Collectionmentioning
confidence: 99%
“…We did not analyze the treatments our patients received before and during their ICU admission, and we therefore cannot determine if women were treated less aggressively or less appropriately than were men. Larger studies 1,2 have shown that compared with men, women are treated more conservatively (ie, fewer invasive procedures, fewer intubations, more code status limitations). However, in our cohort of patients, MEWS before ICU admission, APACHE II scores at the time of ICU admission, and code status limitations did not differ between men and women.…”
Section: Tablementioning
confidence: 99%
“…Other reports have shown sex differentiation outcome is based on etiology; for example, one study reported no differences between sex outcomes in surgical ICUs, although sepsis increased the death rate in females [12,13]. According to above studies, the reasons for higher mortality in women during critical states, despite protective role of estrogen on cardiovascular and immune systems, have been poorly studied.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to susceptibility to bacterial infections, studying the role of sex in the mortality provided contrasting evidence. Some epidemiological studies did not report any gender differences in sepsis-related death (Crabtree et al, 1999;Martin et al, 2003;Laupland et al, 2004;Esper et al, 2006) whereas other found either increased mortality in men (Osborn et al, 2004;Melamed & Sorvillo, 2009;Wafaisade et al, 2011) or women (Combes et al, 2009;Pietropaoli et al, 2010;Nachtigall et al, 2011). As men are also at increased risk of death due to trauma, cancer and cardiovascular diseases as compared with women, the analysis of epidemiological data should integrate these potential biases (Micheli et al, 2009;Pinkhasov et al, 2010;Coronado et al, 2011).…”
Section: Infection Due To Intracellular Bacteria Sex Ratio Referencementioning
confidence: 99%